NS1 Antigen and Immunoglobulin M detection in the Acute and Early Convalescent Stages of Dengue Fever - Ikram, Nadeem Ikram (Journal of Rawalpindi Medical College, 2010)
Background: To evaluate the efficacy of NS1 Antigen assay and Ig M in the diagnosis of dengue virus infection in its acute and early convalescent stages Methods: This prospective study was conducted in the Department of Medicine, DHQ Teaching Hospital Rawalpindi from 1st October 2010 to 10th November 2010. It included all 105 patients who presented with dengue fever during this period. Serum samples of all patients were sent for detection of NS1 Ag, Ig M and Ig G besides other routine investigations. The first four days of clinical illness were taken as the acute stage of the disease while the period from day 5 to day 10 was designated as the early convalescent stage. The efficacy of NS1 Ag and Ig M antibody in both stages was evaluated. Results: The 105 patients comprised of 74 males and 31 females (male to female ratio 2.4:1). Age of patients ranged from 14 to 80 years. Mean age was 33.34 years. Thirty one patients presented in the acute stage of illness while 72 were seen in the early convalescent stage. NS1 antigen was detected in 29 out of 31 patients presenting in the acute stage of dengue infection (93.55%) while Ig M was positive in 7 patients (22.58%). In the early convalescent stage, NS1 antigen was detected in 12 of the 72 patients presenting in this period (16.6%). Ig M was positive in 64 out of 72 patients (88.88%) in this stage. Conclusion: NS1 antigen assay is a very reliable test to diagnose dengue fever in the acute stage of illness. Detection of immunoglobulin M is a dependable test for diagnosis in the early convalescent period of the disease.